Method of sequential evaluation of parameters of the statistical distributing - Заліський, М. Ю.; Соломенцев, О. В. (Problems of Informatization and Control, 2008)
One of algorithms of sequential evaluation of parameters of closeness of probability distribution is considered, basic descriptions of the developed algorithm are certain and analytical formulas are got for their calculation